The Role of the CLIF-C OF and the 2016 MELD in Prognosis of Cirrhosis with and without Acute-on-Chronic Liver Failure - Perdigoto, David N. (2019)
Acute-on-chronic liver failure (ACLF) is defined by the development of acute deterioration of liver function associated with failure of other organs and high short-term mortality in patients with chronic liver disease (CLD). There is no consensus on the diagnostic criteria, and its independence from ordinary decompensation of CLD has frequently been questioned. This study aimed to identify and characterize this condition and to test the CLIF-C OF score comparing it to the 2016-MELD (with sodium) and the Child-Pugh.